Subnational mobilization and the reconfiguration of central-local relations in the shadow of Europe: the case of the Dutch decentralized unitary state. Issue 2 (14th March 2020) - Groenleer, Martijn; Hendriks, Frank
ABSTRACT: The Netherlands is traditionally considered a decentralized unitary state. Recent decentralization of responsibilities from the national to the local level and scaling-up of authority from the local to the city-regional level, accompanied by continuing transfer of tasks to the European Union level, have changed the face of the Dutch state. This article investigates a key question that these developments evoke: what factors, at the national and possibly European levels, drive subnational mobilization and reconfiguration of central-local relations in the case of the Dutch decentralized unitary state? It explores the particular process by which rescaling is taking place in the Netherlands, with 'the region' gaining in importance, as well as the specific combination of historical-institutional and situational-functional factors that – alongside the role of political actors – are driving this process. Updating and complementing previous studies on the Dutch case, the article suggests that these factors of a mainly domestic nature have played a crucial role in the foreground, while 'Europe', as a force of change with regard to subnational mobilization and reconfiguration of central-local relations, has played a background role.